Evolutionary Laws and Stages of the Manufacturing Industry in the World Economy - Balčiūnas, Norbertas (Ekonomika, 1997)
In this paper the interrelation between the share of the manufacturing industry and the development level (per capita level of GNP) of the country and adequate regularities are separated into three stages: commoditybased economy, commoditybased/financial economy, and financial/commoditybased economic development. The evolutionary laws and stages are examined in developed countries of the world. newly emerging industrial countries, small countries of Western Europe, and other developing countries in the period 1955–91. A sharp decline of the Lithuanian manufacturing industry and decrease in the per capita level of the GNP in the period 1989-94, the inefficient restructuring of the manufacturing industrial sector, and the necessity to form structural policy and priorities for Lithuanian industry are analysed in detail. In this paper we investigate the development of transnational corporations as an essential and definite manifestation of the globalisation process within the period of 25 years and their economic potential and influence for developing countries.